APPORT DE LA TÉLÉDÉTECTION À L’ÉTUDE DE LA DYNAMIQUE SÉDIMENTAIRE AU SEIN DE LA LAGUNE OUALIDIA (MAROC) - Taghia Yamna; Algouti Abdellah; Algouti Ahmed; Kheir Addine Azzaoui; Ali Ayyda (European Scientific Journal, ESJ, 2014)
To study sedimentary dynamics in the Oualidia lagoon and to explain its morphological evolution in time, analysing aerial photos and Landsat imagery was carried out since 1962 up to 2013. The study reveals a formation of the erosional zones and sedimentary accretions, evolving in time, thus, the position of the main channel and that of the “sand area” changes permanently and progressively, according to the form channel and the hydrodynamic parameters reigning in the lagoon.